Gamophobia in Generation Z: Analysis of Psychological, Social, and Economic Factors from The Perspective of Islamic Family Law (A Study in Sukajadi Village, Bumi Ratu Nuban, Central Lampung) - Satria Pranata; Habib Sulthon Asnawi; Ahmad Muslimin (Assyfa Journal of Islamic Studies, 2026)
The phenomenon of gamophobia or fear of marriage is increasingly concerning among Generation Z, including in rural areas. This study aims to analyze the psychological, social, and economic factors influencing gamophobia in Generation Z and its relevance to Islamic Family Law. The research employed a descriptive qualitative approach with field research type in Sukajadi Village, Bumi Ratu Nuban, Central Lampung. Data collection techniques included non-participatory observation, in-depth interviews with 10 informants (village head, religious leaders, community leaders, parents, and Generation Z), and documentation. Data analysis used data reduction, data display, and conclusion verification. The results showed that gamophobia in Generation Z was at mild to moderate levels, characterized by anxiety when discussing marriage, overthinking, and low self-confidence. Dominant psychological factors included family trauma and fear of failure; social factors included social media influence and individualistic lifestyle; economic factors included job instability and high wedding costs. From the Islamic Family Law perspective, gamophobia is relevant as a form of caution but contradicts Islamic principles if excessive to the point of avoiding marriage without valid sharia reasons. This study recommends an integrated premarital guidance program.